SISTEM MATA PENCAHARIAN MASYARAKAT PETANI DI LAHAN GAMBUT (Studi Pada Masyarakat Desa Sungai Tohor, Kecamatan Tebing Tinggi, Kabupaten Kepulauan Meranti) - Sofia Aisya; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The research was conducted in the Sungai Tohor Village Tebing Tinggi Sub-District Kepulauan Meranti Regency with problems (1) How the life of the farmers’ peat in the land managing? (2) How farmer's community livelihoods systems especially since fires break out of the forest and land in 2014? The purpose of this research is to explain the opening process to make agricultural land by farmers, and to know what do the farmer in the peat land, so it can be the peat land as the source of life Sungai Tohor Village Tebing Tinggi Sub-District Kepulauan Meranti Regency. This is a qualitative research. The subject in this research is the society figure who know the history of the peat opening to be agriculture land and he able to explain the problems researched. To collect the data, researcher use the interview hints and documentation. The result of the research show that the farmer community in peat land at the first time to be agriculture land, has a local wisdom. So that in opening the peat land the farmer not damage the environment. And they plant sago as the farmers’ community livelihoods when the event of fire who spent their land. As the effort of farmer to keep the land from fire they use canal blocking (sekat kanal), to cultivate their plantations, they replant sago as the local wisdom in Sungai Tohor Village. The additional information is the young man chose the appropriate working outside the village for some reason. Though this village is rich of local wisdom with gained hereditary and a special farmer which is not only processing and caring for their land with existing local wisdom to stay awake.Keywords: Peat Farmers. Sungai Tohor